Implementation of Big Book Fantasy Stories as a Medialearning in Improving Abilities Reading The Beginning for Students SDN 01 Rantau Selatan Labuhan Batu - Mayrika Hutagalung, Ade; Sutikno; Kartolo, Rahmat (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the implementation of Big Book learning media in improving the beginning reading skills of first-grade students at SDN 01 Rantau Selatan, Labuhan Batu Regency. The main problem raised in this study is the low beginning reading skills of students and the lack of use of interesting and effective learning media. Therefore, this study was conducted to determine the effectiveness of Big Book in improving students' reading skills. The research method used was a quantitative method with a pretest-posttest experimental design. The research sample consisted of 23 first-grade students selected using a saturated sampling technique. Data were collected through an beginning reading test given before and after treatment using Big Book media. The results showed a significant increase in students' beginning reading skills after the use of Big Book. The average pretest score of students was 48.69, with a standard deviation of 17.91, indicating that most students had low to moderate beginning reading skills. After being given treatment, the average posttest score increased to 69.13 with a standard deviation of 10.83, indicating an increase of 20.44 points. In addition, the distribution of score categories also experienced changes, where in the pretest only 17.39% of students were in the high category, while in the posttest it increased to 30.43%. The t-test results showed that the calculated t of 8.095 was greater than the t table, so it can be concluded that there was a significant difference between the pretest and posttest scores after the application of Big Book media in early reading learning. Thus, this study proves that the use of Big Book media can significantly improve students' early reading skills